The Self-Efficacy and Kluckhohn's Value Orientations: Core Behavioral Drivers Among Young Tobacco Farmers in Temanggung - Dewi Fortuna, Puri Eka; Hariadi, Sunarru Samsi; Lasiyo; Widiarso, Budi Purwo (Jurnal Pengembangan Penyuluhan Pertanian, 2025)
This study analyzes the primary drivers of tobacco farming behavior among young farmers in Temanggung Regency, Indonesia’s premium tobacco hub. Integrating psycho-cultural approaches—self-efficacy theory (Bandura, 1986) and Kluckhohn’s (1951) cultural value orientation—this research challenges conventional agricultural behavior theories emphasizing environmental factors. Data were collected through a survey of 140 young farmers across 6 core districts, analyzed using Structural Equation Modeling (SEM) and profitability assessment. Key findings reveal Personal factors (particularly self-efficacy: λ=0.743) significantly influence behavior (β=0.706; p<0.01), while environmental factors are insignificant (β=0.147). Kluckhohn’s values especially mastery over nature (mountain land expansion without terracing) and work for livelihood reinforce self-efficacy through cultural internalization. Loyalty among young farmers stems from inherited land ownership (77.14%) and high profitability (R/C ratio 1.44). These findings revise Ajzen’s (1991) theory and propose a "psycho-cultural resilience" model for farmer regeneration, where strengthening self-efficacy and conserving local values prove more effective than external interventions.